2010
DOI: 10.1016/j.ibmb.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroid regulation of ovarian growth and oocyte maturation in the red flour beetle, Tribolium castaneum

Abstract: Previous studies from our laboratory showed the involvement of juvenile hormone (JH) and ecdysteroid signaling in the regulation of female reproduction in the red flour beetle, Tribolium castaneum. JH regulates vitellogenin (Vg) synthesis in the fat body but the role of ecdysteroid signaling is not known. Here, we report on ecdysteroid regulation of ovarian growth and oocyte maturation. Microarray analysis of RNA isolated from ovaries showed the up-regulation of several genes coding for proteins involved in ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 40 publications
3
100
0
Order By: Relevance
“…Similar observations were reported from EcR knock-down studies of T. castaneum, where a 50-75% reduction in the vitellogenin transcript level resulted in a decrease in egg development (Xu et al, 2010). Moreover, development of a follicular cell layer necessary for oocyte maturation was disrupted, resulting in an arrest of the oocyte in the pre-vitellogenic stage (Parthasarathy et al, 2010). The same observations had previously been recorded in D. melanogaster where EcR deficiency resulted in abnormal egg chamber development and loss of vitellogenic stages (Carney and Bender, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…Similar observations were reported from EcR knock-down studies of T. castaneum, where a 50-75% reduction in the vitellogenin transcript level resulted in a decrease in egg development (Xu et al, 2010). Moreover, development of a follicular cell layer necessary for oocyte maturation was disrupted, resulting in an arrest of the oocyte in the pre-vitellogenic stage (Parthasarathy et al, 2010). The same observations had previously been recorded in D. melanogaster where EcR deficiency resulted in abnormal egg chamber development and loss of vitellogenic stages (Carney and Bender, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…In the adult stage, ecdysteroids are mainly synthesized in the gonads (Brown et al, 2009), although other tissues have been suggested as additional sources of ecdysteroids in some insect species (e.g., Delbecque et al, 1990; Gillot and Ismail, 1995). Ecdysteroids have autocrine and paracrine regulatory roles in ovary and oocyte development, since they control ovary morphogenesis, differentiation of germ line stem cells and development of follicle cells (Parthasarathy et al, 2010; Gancz et al, 2011; Konig et al, 2011; Ting, 2013). In addition, conjugates are stored in the eggs as an embryonic source of ecdysteroids.…”
Section: The Isp and Female Reproductive Physiologymentioning
confidence: 99%
“…cDNA synthesis and qRT-PCR reactions were performed using the genespecific primers (reported in Refs. 19 -21 or shown in Table 1) and methods described previously (19,20). Ribosomal protein gene rp49 was used as an internal control in qPCR analysis.…”
Section: Namementioning
confidence: 99%